MULTIPROJECT REPORT TO INCREASE RILEY COUNTY HEALTH DEPARTMENT PUBLIC HEALTH PROFESSIONAL INTERCONECTIVITY - Kucera, Anna (My University, 2021)
There is a need for a strong interconnection between public health professionals to provide fluid and cohesive responses to changes in community or disease trends. These public health professionals include those currently in the public heath workforce, those soon to be entering the public heath workforce, and those in the general population. The need for interconnection becomes even more essential during pandemics. Three ways that were identified to accomplish increased interconnectivity are by surveying current health care professionals, developing an Academic Heath Department (AHD), and providing educational fliers. Surveying health care professionals allow health departments to enhance relationships with professionals by understanding attitudes toward procedures, identify gaps in knowledge for disease reporting or programs available, and provide resources or programs as needed to aid these workers in their essential duties. An AHD agreement enhances the partnership of a health department and university in the proximity to create a mutually beneficial partnership. An AHD partnership allows for shared resources, enhanced student learning, relevant research, and readily available health department continuing education. Three preparatory documents were created for Riley County Health Department to expedite the formation of an AHD with Kansas State University Master of Public Health Department. These documents provided templates for legal formation of the AHD, timelines and recommendations based on literature review, and evaluation of current resources. A cross-sectional study was designed to identify reasons for disease underreporting among health care professionals. Additionally, two fliers were created for the Kansas State University Master of Public Health Program regarding COVID-19 for evaluation and use on website displays for the education of the general population.
Keywords: AHD; RCHD; survey; Covid-19